1989
DOI: 10.1200/jco.1989.7.12.1863
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with interleukin-2 and alpha-interferon for the treatment of patients with advanced cancer.

Abstract: We performed an escalating dose study of the combined administration of interleukin-2 (IL-2) and alpha-interferon (alpha-IFN) in 94 patients with metastatic cancer. Patients received alpha-IFN at a dose of 3 x 10(6) U/m2 in conjunction with IL-2 at doses of either 1 x 10(6) U/m2 (six patients), 3 x 10(6) U/m2 (32 patients), or 4.5 x 10(6) U/m2 (26 patients). Thirty patients received alpha-IFN at 6 x 10(6) U/m2 plus IL-2 at 4.5 x 10(6) U/m2. Patients each received cytokine as an intravenous bolus infusion every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(81 citation statements)
references
References 28 publications
2
78
1
Order By: Relevance
“…Biological therapy with combined IEN-a and IL-2 may result in synergistic interactions, with enhanced antigen presentation due to IFN-a-mediated up-regulation of class 1 MHC molecules and consequent improvement in tumour recognition by IL-2-stimulated cytotoxic T cells. In early non-randomized trials, the combination of both agents as sole therapy for metastatic melanoma appeared to be superior to either agent alone (Rosenberg et al, 1989), although this was not confirmed in a subsequent randomized phase III trial of high-dose intravenous IL-2 with or without IFN-a (Sparano et al, 1993). The addition of biological therapy with both IL-2 and IFN-a to chemotherapy may prove effective because of the lack of cross-resistance, as the mechanisms of resistance are different between these modes of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Biological therapy with combined IEN-a and IL-2 may result in synergistic interactions, with enhanced antigen presentation due to IFN-a-mediated up-regulation of class 1 MHC molecules and consequent improvement in tumour recognition by IL-2-stimulated cytotoxic T cells. In early non-randomized trials, the combination of both agents as sole therapy for metastatic melanoma appeared to be superior to either agent alone (Rosenberg et al, 1989), although this was not confirmed in a subsequent randomized phase III trial of high-dose intravenous IL-2 with or without IFN-a (Sparano et al, 1993). The addition of biological therapy with both IL-2 and IFN-a to chemotherapy may prove effective because of the lack of cross-resistance, as the mechanisms of resistance are different between these modes of therapy.…”
Section: Methodsmentioning
confidence: 99%
“…About 20% to 40% of patients develops a metastatic disease after nephrectomy (3) and lung is one of the sites most frequently affected by RCC metastases (second after liver) (4). Patients that receive no treatment for metastatic RCC (mRCC) have a 0-18% 5-year survival (5). Nonsurgical therapy for mRCC has limited efficacy, with a median overall survival (OS) reported between 26.4 and 32.0 months (6,7) for mRCC patients receiving several agents targeting angiogenesis or the mTOR pathway, in addition to traditional chemotherapeutic regimens and immunotherapy (8).…”
Section: Introductionmentioning
confidence: 99%
“…Its main role at present is in the treatment of metastatic renal cell carcinoma and malignant melanoma, where IL-2 has been used alone and also in combination with other agents such as interferon, lymphokine-activated killer (LAK) cells or tumour-infiltrating lymphocytes (TIL). Documented response rates in renal cell carcinoma and malignant melanoma in patients treated with IL-2, or with combinations of IL-2 and one of the above agents, range from 20-40% Rosenberg et al, 1989). Treatment with IL-2 is associated with a well-documented range of side-effects (Lotze et al, 1986b;Parkinson, 1988;Lotze et al, 1986a Statistical analysis Differences in survival between groups were analysed using a log-rank test.…”
mentioning
confidence: 99%